Analisis Pengaruh Inflasi, Investasi, Upah Minimum DanPertumbuhan Ekonomi Terhadap Pengangguran Di EkskarisidenanSurakarta Periode Tahun 2010-2014 - Putri, Titis Sudhani; , Ir. Maulidyah Indira Hasmarini M.S (2017)
This study aimed to analyze the effect of inflation, Investment, Economic Growth, Minimum Wage on Unemployment Rate in Ex-Surakarta karisidenan period 2010-2014. The data used is data panel to take the 7 regencies / cities contained in Surakarta Karisidenan with a time series of five years (2010-2014). Through secondary data drawn from the literature either CPM literature, journals and previous research. The data is processed using panel data with the selected method is a method of analysis Pooled Least Square (PLS), assisted by the Eviews7 software in operation.The results of this study indicate variables Economic Growth (GDP) and the minimum wage (UMK) significantly influence the unemployment rate in the Ex-Surakarta karisidenan period 2010-2014 at a significance level of 5%. While the variable inflation and investments are not significantly influence the unemployment rate in the Ex-Surakarta karisidenan period 2010-2014 at a significance level of 5%.